PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP KINERJA GURU DALAM MENINGKATKAN MUTU AKADEMIK LULUSAN PADA SMA RSBI DI KABUPATEN SIDOARJO - Solichin, M. Riadhos (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2013)
This research investigates the effect of job satisfaction and job stress on the teachers performance in enhancing graduates academic achievement in internationally standardized senior highs schools in Sidoarjo. 60 teachers of grade XII teaching the nationally tested subjects were purposefully taken as the sample of the study. Data were gathered by using questionnaire and analysed by employing Partial Least Square Analysis (PLS) in the SmartPLS software. The finding indicates that there is a positive relationship between job satisfaction and teachers performance. It is predicted that job satisfaction play important role in enhancing the graduates academic achievement. Secondly, there is contrast relationship between the job stress and teachers performance. In other words, teachers still work hard in enhancing their students academic achievement regardless their job stress.